Plant variety protection: upholding breeders’ rights - Tan, S.L.; Soo, F.L. (UTAR Agriculture Science Journal, 2016)
Plant breeders can now obtain intellectual property rights in Malaysia to protect their efforts in the breeding and development of new plant varieties.